Disaster Education and Social Media Use Influence Disaster Preparedness in Coastal Communities - Falih Ijlal Septian; Edwin Rizal; Ute Lies Siti Khadijah; Rully Khairul Anwar (UIN Sunan Gunung Djati, 2024)
This study aims to examine the impact of disaster education and social media usage on disaster preparedness in coastal communities, focusing on Masawah Village in the Cimerak District, Pangandaran Regency. The research was conducted using a quantitative survey method with data collected from a sample of 100 respondents selected through probability sampling with a cluster sampling approach. Data were analysed using Partial Least Squares (PLS) with SmartPLS 3.0 software. The findings reveal that both disaster education and social media usage significantly influence individual intentions and actual disaster preparedness. Additionally, the mediating role of intention is identified, highlighting its importance in linking disaster education and social media usage to preparedness. These results suggest that disaster education should incorporate practical training and community participation, while social media campaigns should leverage popular platforms like WhatsApp and TikTok to engage wider audiences effectively. This study contributes to the literature by integrating the Theory of Planned Behavior (TPB) to explore the mediating effects of intention in disaster preparedness. It offers practical implications for policymakers and disaster management organisations to enhance community readiness. The originality of this research lies in its focus on a coastal community and its use of TPB as a theoretical framework, addressing gaps in previous studies that have not thoroughly investigated the role of social media in disaster preparedness.